N‐cadherin cleavage: A critical function that induces diabetic retinopathy fibrosis via regulation of β‐catenin translocation. Issue 4 (20th March 2023) - Xiang, Wei; Li, Longhui; Hong, Fuyan; Zeng, Yongcheng; Zhang, Jin; Xie, Jinye; Shen, Gang; Wang, Jinhong; Fang, Zhenzhen; Qi, Weiwei; Yang, Xia; Gao, Guoquan; et al.
Abstract: Retinal fibrosis is a severe pathological change in the late stage of diabetic retinopathy and is also the leading cause of blindness. We have previously revealed that N‐cadherin was significantly increased in type 1 and type 2 diabetic mice retinas and the fibrovascular membranes from proliferative diabetic retinopathy (PDR) patients. However, whether N‐cadherin directly induces retinal fibrosis in DR and the related mechanism is unknown. Here, we investigated the pathogenic role of N‐cadherin in mediating retinal fibrosis and further explored the relevant therapeutic targets. We found that the level of N‐cadherin was significantly increased in PDR patients and STZ‐induced diabetic mice and positively correlated with the fibrotic molecules Connective Tissue Growth Factor (CTGF) and fibronectin (FN). Moreover, intravitreal injection of N‐cadherin adenovirus significantly increased the expression of FN and CTGF in normal mice retinas. Mechanistically, overexpression of N‐cadherin promotes N‐cadherin cleavage, and N‐cadherin cleavage can further induce translocation of non‐p‐β‐catenin in the nucleus and upregulation of fibrotic molecules. Furthermore, we found a novel N‐cadherin cleavage inhibitor, pigment epithelial‐derived factor (PEDF), which ameliorated the N‐cadherin cleavage and subsequent retinal fibrosis in diabetic mice. Thus, our findings provide novel evidence that elevated N‐cadherin level not only acts as a classic EMT maker but also plays a causative role in diabetic retinal fibrosis, and targeting N‐cadherin cleavage may provide a strategy to inhibit retinal fibrosis in DR patients. Abstract : Schematics show the working model of N‐cadherin cleavage‐enhanced retinal fibrosis in DR. In diabetic retinopathy, N‐cadherin is upregulated, leading to N‐cadherin cleavage, producing CTF2 fragment. CTF2 binds to β‐catenin and translocates the nucleus together, leading to the upregulation of Fibronectin and CTGF, which finally causes retinal fibrosis. However, PEDF, which serves as the upstream regulator of N‐cadherin cleavage, inhibits N‐cadherin cleavage by suppressing MMP9 and PS1, thus playing a role in alleviating DR fibrosis.